Age-related decrease in motor cortical inhibition during standing under different sensory conditions - Papegaaij, Selma; Taube, Wolfgang; Hogenhout, Margot; Baudry, Stéphane; Hortobágyi, Tibor (Frontiers in Aging Neuroscience, 2014)
Background Although recent studies point to the involvement of the primary motor cortex in postural control, it is unknown if age-related deterioration of postural control is associated with changes in motor cortical circuits. We examined the interaction between age and sensory condition in the excitability of intracortical motor pathways as indexed by short-interval intracortical inhibition (SICI) and intracortical facilitation (ICF) during standing. Methods We used magnetic brain stimulation to evoke SICI and ICF in 11 young (range 21-25 years) and 12 healthy old adults (range 60-74 years) while they stood on a rigid platform or foam, with the eyes open or closed. Results There was an overall age-related 43% reduction in SICI (p = 0.001). SICI lessened when standing on foam in old (31%) but not in young (1%) adults (condition x group interaction, p = 0.049). This reduction was associated with increases in center of pressure velocity (r = -0.648, p = 0.043). Age (p = 0.527) and sensory conditions (p = 0.325) did not affect ICF. Conclusions Motor cortical circuits are modulated differently in healthy old vs. young adults during the control of upright posture. Future experiments will clarify whether this difference in control mediates impaired postural control or serves as a compensatory mechanism to counteract postural instability.